FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG - NOVICE LIANTO; BUDI HARTONO KUSUMA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The aim of this research is to examine the influence of profitability, solvability, firm size, age of the company, and industrial sector on the audit report lag. This research used 28 consumer goods industry companies and 11 multifinance companies listed in Indonesian Stock Exchange, selected using purposive sampling method during 2004 until 2008. The hypothesis proposed were tested by multiple linier regression models. The result shows profitability, solvability, and age of the company have influence on audit report lag. On the other hand, firm size and industrial sector have no influence on audit report lag.